Causes of Supply Chain Disruptions: An Empirical Analysis in Cold Chains for Food and Pharmaceuticals - Brenner, Verena (Springer, 2015)
Verena Brenner provides a systematic approach for the investigation, measurement, and management of supply chain disruptions. A terminological, theoretical and practical basis for the analysis of supply chain disruptions is developed to create a consistent and transferable research framework. To better understand why certain supply chains are more susceptible to disruptions than others, this framework is then tested empirically in cold chain logistics. Based on a survey with approximately 60 supply chain specialists from production, distribution and retail of food and pharmaceuticals, drivers for resilience and vulnerability of supply chains are identified by comparing how partnerships and transactions were organized. Thereby, strategies for assuring the robustness of supply chains are depicted and connections to company-internal risk management are highlighted.